Effect of different biochar particle sizes together with bio-organic fertilizer on rhizosphere soil microecological environment on saline–alkali land - Gu, Yin-yu; Zhang, Hai-yang; Liang, Xiao-yan; Fu, Rao; Li, Meng; Chen, Chuan-jie (Frontiers in Environmental Science, 2022)
The application of biochar and bio-organic fertilizers (BOFs) is effective for improving soil ecological environments. However, soil physico-chemical properties and the microbiome diversity of rhizosphere soil after the application of different sized particles of biochar together with BOF in saline-alkali land have not been thoroughly described. A field experiment was performed to investigate the effects of different sized particles of apple shoot biochar (60, 30, and 10 mesh) together with BOF on soil bacteria (using Illumina high-throughput sequencing) and the physico-chemical properties of Mesembryanthemum cordifolium L. f. grown on saline-alkali land. Results indicated that the combined application of BOF and 10 mesh to 60 mesh biochar reduced the volumetric weight of soil by 14% to 29%, respectively, and additionally decreased soil electrical conductivity, increased the aerial biomass of the M.cordifolium L. f. by over 30% and notably improved soil water-holding capacity, with 60 mesh giving the best results; organic carbon (OC), organic matter (OM), total nitrogen (N), available phosphorus, alkaline nitrogen, total potassium (K), and total phosphorus (P) were all significantly increased by the addition of combined biochar and BOF, thereinto field capacity, N, P, K, OC, and OM were positively correlated with the bacterial community structure of co-applied biochar and BOF. There were no significant differences in the richness of total bacteria among the treatments; Proteobacteria, Actinobacteria, and Chloroflexi accounted for >70% of the total bacteria in each treatment, Norank_f__Geminicoccaceae and Micromonospora was the dominant genera across the treatments. The findings suggested that plant growth, physico-chemical properties and community diversity of rhizosphere bacteria in saline-alkali land were significantly positively influenced by biochar 60 mesh plus BOF, followed by biochar 10 and 30 mesh plus BOF. This conclusion could facilitate the study of the ecological functions of biochar and BOF, as well as their interactions with salt-tolerant plant on saline-alkali soil, which can be used to provide exploration ideas for saline-alkali land improvement.